Development of an Ackermann-type Mobile Platform for the Validation of Autonomous Navigation Algorithms within the ESPOCH Campus - Barahona, Andres; Rios, Kleber; Gavilanes, Javier; Gavilanes, Johnny (ESPOCH congresses, 2022)
The continual development of the automotive industry has evolved to astronomical levels, capable of promoting a new technological generation of several automated systems (both mechanical and electronic systems). As a result, a generation of autonomous vehicles – also known as intelligent vehicles – capable of avoiding human errors has emerged. In the present investigation, an Ackermann-type mobile prototype is used to validate autonomous navigation algorithms in different environmental conditions, which is developed by covering artificial vision stages such as the detection of the bicycle lane and traffic signals at scale. The control system consists of three parts – First is the detection algorithm through an artificial vision to collect information from the environment through a Pi camera that can later be processed through Python with its OpenCV tool. The second deals with the training of traffic signs (Stop and Speed Signage) through the Haar Cascade, as well as the detection of road lines through which various filters such as Canny, edge detection, and the transformation of Hough are executed on the Python platform with the OpenCV tool. The third part is the communication between the processing of the codes and their respective actuators (Motor, Servomotor) to finally collect the statistical data and validate the algorithms in the Ackerman-type mobile prototype. Keywords: Python, OpenCV, Canny Filter, Hough Transform, Haar Cascade. Resumen El desarrollo constante de la industria automotriz evoluciono a niveles astronómicos capaz de impulsar una nueva generación tecnológica de automatización de varios los sus sistemas ya sean: mecánicos o electrónicos y así forma la generación de vehículos autónomos o llamados también vehículos inteligentes, capaces de evitar errores humanos al conducir. En la presente investigación se implementa un prototipo móvil tipo Ackermann para validar algoritmos de navegación autónoma en diferentes condiciones de su entorno que se desarrolle cubriendo etapas de visión artificial como la detección del carril de una ciclovía y señales de tránsito a escala. El sistema de control consta de tres partes, la primera parte es el algoritmo de detección por medio de visión artificial para recolectar información del entorno a través de una cámara Pi y posteriormente ser procesada a través de Python con su herramienta OpenCV. La segunda parte se encarga del entrenamiento de las señales de tránsito (Pare y Señalética de Velocidad) por medio de Haar cascade, además la detección las líneas de la carretera las cuales a través. de varios filtros como Canny, detección de bordes y la transformada de Hough todos estos filtros se lo ejecutan en la plataforma de Python con la herramienta de OpenCV, y la tercera parte es la comunicación entre el procesamiento de los códigos a sus respectivos actuadores (Motor, Servomotor) para finalmente recolectar datos estadísticos y Validar los algoritmos en el prototipo móvil tipo Ackerman. Palabras Clave: Python, Open, Filtro Canny, Tranformada de Houg, Haar Cascade.